Coding for Optical Channels - Djordjevic, Ivan.; Ryan, William; Vasic, Bane.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Coding for Optical Channels Ivan Djordjevic William Ryan Bane Vasic In order to adapt to the ever-increasing demands for high-speed transmission and distance-independent connectivity, today$1 (Bs network operators are implementing 100 Gb/s per dense wavelength division multiplexing (DWDM) channel. At those data rates, the performance of fiber-optic communication systems is degraded significantly due to intra- and inter-channel fiber nonlinearities, polarization-mode dispersion (PMD), and chromatic dispersion. In order to deal with these channel impairments, novel advanced techniques in modulation, detection, coding and signal processing are needed. This groundbreaking book represents a coherent and comprehensive introduction to the fundamentals of optical communications, digital signal processing (DSP), and coding for optical channels. This book: Is the first to integrate the fundamentals of coding theory and DSP with the fundamentals of optical communication; Provides detailed coverage of joint coding and modulation for optical communications; Presents turbo equalization for joint iterative channel equalization and soft decoding on optical channels; Provides in-depth coverage of codes on graphs, including LDPC and turbo codes, and describes their application to optical channels; Includes coverage of both fiber-optics and free-space optical (FSO) channels; Is the first to cover the channel capacity of fiber-optic communication systems; Is the first to describe constrained coding for optical channels.s
Fundamentals of Optical Communication -- Channel Impairments and Optical Communication Systems Engineering -- Channel Coding for Optical Channels -- Graph-Based Codes -- Coded Modulation -- Turbo Equalization in Fiber-Optics Communication Systems -- Constrained Coding for Optical Communication -- Coding for Free-space Optical Channels -- Optical Channel Capacity -- Future Research Directions in Coding for Optical Channels.
Keywords: Engineering; Microwaves; Optical engineering; Electrical engineering; Engineering; Communications Engineering, Networks; Signal, Image and Speech Processing; Microwaves, RF and Optical Engineering; Electronic books